Maternal sleep duration and neonatal birth weight: the Japan Environment and Children's Study - Tsuyoshi Murata; Hyo Kyozuka; Toma Fukuda; Shun Yasuda; Akiko Yamaguchi; Seiichi Morokuma; Akiko Sato; Yuka Ogata; Kosei Shinoki; Mitsuaki Hosoya; Seiji Yasumura; Koichi Hashimoto; et al. (BMC, 2021)
Abstract Background The adequate maternal sleep duration required for favorable obstetric outcomes is unknown. We evaluated the association between maternal sleep duration and low birth weight infants, small for gestational age infants, and macrosomia. Methods Participants enrolled in the Japan Environment and Children's Study, a nationwide birth cohort study, with singleton pregnancies after 22 weeks, who gave birth between 2011 and 2014 were enrolled and categorized into five groups according to maternal sleep duration during pregnancy: < 6.0 h, 6.0-7.9 h, 8.0-8.9 h, 9.0-9.9 h, and 10.0-12.0 h. We evaluated the association between maternal sleep duration and the incidence of low birth weight infants (< 2500 g), very low birth weight infants (< 1500 g), small for gestational age infants, and macrosomia (> 4000 g), with women with maternal sleep duration of 6.0-7.9 h as the reference, using a multiple logistic regression model. Results In total, 82,171 participants were analyzed. The adjusted odds ratios (95% confidence intervals) for low birth weight infants in women with maternal sleep duration of 9.0-9.9 h and 10.0-12.0 h and for small for gestational age infants in women with maternal sleep duration of 9.0-9.9 h were 0.90 (0.83-0.99), 0.86 (0.76-0.99), and 0.91 (0.82-0.99), respectively, before adjusting for excessive gestational weight gain. No significant association was observed between maternal sleep duration and these outcomes after adjusting for excessive gestational weight gain. Among women with appropriate gestational weight gain, the adjusted odds ratios (95% confidence intervals) for low birth weight infants and for small for gestational age infants with sleep duration of 9.0-9.9 h were 0.88 (0.80-0.97) and 0.87 (0.78-0.97), respectively. Conclusions Maternal sleep duration of 9.0-9.9 h was significantly associated with the decreased incidence of low birth weight infants and small for gestational age infants in pregnant women with appropriate gestational weight gain, compared with that of 6.0-7.9 h. Care providers should provide proper counseling regarding the association between maternal sleep duration and neonatal birth weight and suggest comprehensive maternal lifestyle modifications to prevent low birth weight and small for gestational age infants.